Innovating healthcare delivery to address noncommunicable diseases in low-income settings: the example of hypertension. (July 2016) - Piot, Peter; Aerts, Ann; Wood, David A; Lamptey, Peter; Oti, Samuel; Connell, Kenneth; Dorairaj, Prabhakaran; Boufford, Jo I; Caldwell, Aya; Perel, Pablo
London Dialogue event, The Hospital Club, 24 Endell St, London, WC2H 9HQ, London, UK, 1 December 2015 Hypertension is a global health issue causing almost 10 million deaths annually, with a disproportionate number occurring in low- and middle-income countries. The condition can be managed effectively, but there is a need for innovation in healthcare delivery to alleviate its burden. This paper presents a number of innovative delivery models from a number of different countries, including Kenya, Ghana, Barbados and India. These models were presented at the London Dialogue event, which was cohosted by the Novartis Foundation and the London School of Hygiene & Tropical Medicine Centre for Global Noncommunicable Diseases on 1 December 2015. It is argued that these models are applicable not only to hypertension, but provide valuable lessons to address other noncommunicable diseases.